CPKCγ‐mediated down‐regulation of UCHL1 alleviates ischaemic neuronal injuries by decreasing autophagy via ERK‐mTOR pathway. Issue 12 (20th July 2017) - Zhang, Dan; Han, Song; Wang, Shizun; Luo, Yanlin; Zhao, Li; Li, Junfa
Abstract: Stroke is one of the leading causes of death in the world, but its underlying mechanisms remain unclear. Both conventional protein kinase C (cPKC)γ and ubiquitin C‐terminal hydrolase L1 (UCHL1) are neuron‐specific proteins. In the models of 1‐hr middle cerebral artery occlusion (MCAO)/24‐hr reperfusion in mice and 1‐hr oxygen–glucose deprivation (OGD)/24‐hr reoxygenation in cortical neurons, we found that cPKCγ gene knockout remarkably aggravated ischaemic injuries and simultaneously increased the levels of cleaved (Cl)‐caspase‐3 and LC3‐I proteolysis product LC3‐II, and the ratio of TUNEL‐positive cells to total neurons. Moreover, cPKCγ gene knockout could increase UCHL1 protein expression via elevating its mRNA level regulated by the nuclear factor κB inhibitor alpha (IκB‐α)/nuclear factor κB (NF‐κB) pathway in cortical neurons. Both inhibitor and shRNA of UCHL1 significantly reduced the ratio of LC3‐II/total LC3, which contributed to neuronal survival after ischaemic stroke, but did not alter the level of Cl‐caspase‐3. In addition, UCHL1 shRNA reversed the effect of cPKCγ on the phosphorylation levels of mTOR and ERK rather than that of AMPK and GSK‐3β. In conclusion, our results suggest that cPKCγ activation alleviates ischaemic injuries of mice and cortical neurons through inhibiting UCHL1 expression, which may negatively regulate autophagy through ERK‐mTOR pathway.